Nowy Francuski Ekstremizm — próba definicji, charakterystyka, przedstawiciele - Filip Grzędowski (Studia Filmoznawcze)
The author describes the New French Extremity, a trend of French transgressive films initiated in the 1990s. In his text, the author, on the basis of critical and film texts and previous publications, attempts to create a unified definition. NFE films are characterized by distancing the viewer, brutality and graphic portrayal of violence. The most common themes are the body and violence. The author draws attention to the inspiration of B-grade cinema, horror films and the inextricable artistic setting.